2010
DOI: 10.1111/j.1365-3121.2010.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between fault scarps and shorelines: the question of the nature of the Kahrizak, North Rey and South Rey features in the Tehran plain (Iran)

Abstract: International audienceP>Tehran is one of the largest cities in the world (12 million people) facing seismic hazard. Standing at the foothills of Alborz Mountains, the capital of Iran is exposed to potential earthquakes associated with several nearby active faults. Classically mentioned as active features, the Kahrizak, the North Rey and the South Rey scarps cross the town itself and would be the sources of several destructive historical earthquakes. However, the nature of these topographic scarps remains uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…This result is obviously in direct contradiction to the views of some of earlier workers on the geometry and mechanism of movement of the Kahrizak fault. Our results clearly show that the Kahrizak scarp is not a sedimentary feature (i.e., shoreline) as recently suggested by Nazari et al (2009) but formed due to displacement of a genuine fault at depth. Moreover, it is not a reverse fault dipping north as suggested by Berberian et al (1985) based on interpreting the shape of the fault trace at the surface.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This result is obviously in direct contradiction to the views of some of earlier workers on the geometry and mechanism of movement of the Kahrizak fault. Our results clearly show that the Kahrizak scarp is not a sedimentary feature (i.e., shoreline) as recently suggested by Nazari et al (2009) but formed due to displacement of a genuine fault at depth. Moreover, it is not a reverse fault dipping north as suggested by Berberian et al (1985) based on interpreting the shape of the fault trace at the surface.…”
Section: Discussionsupporting
confidence: 47%
“…Paleoseismological investigations across the Kahrizak fault, however, indicated that the Kahrizak fault forms a subvertical right-lateral fault (DeMartini et al 1998). Recent works by Nazari et al (2009) suggest that the Kahrizak escarpment is not a structural feature but represents the shoreline of an old lake in the south of Tehran.…”
Section: Introductionmentioning
confidence: 94%
“…The existence of the Pardisan fault (which has also been called the Milad Tower thrust or foreberg in some studies) has previously been acknowledged (e.g. Jackson 2008;Abbassi & Farbod 2009;Landgraf 2010;Nazari et al 2010;Ritz et al 2012), but our present study presents the first detailed geomorphic analysis and estimate of its slip-rate. The OSL samples analysed in our study were collected in 2008, shortly before the exposures in the vicinity were completely masked or destroyed by urban activities.…”
Section: Introductionmentioning
confidence: 78%
“…1c) are present along strike to the west of the Parchin thrust, within the alluvial Tehran plain. Nazari et al (2010) inferred an absence of activity on all three of these scarps from the lack of deformation of sediment layers exposed in trenches across the scarps. They instead interpret the scarps as palaeolake shorelines.…”
Section: Active Faulting In the Tehran Regionmentioning
confidence: 99%
“…NTF: North Tehran Fault, TF: Taleghan Fault, MF: Mosha Fault, AQF: Abyek‐Qazvin Fault, AF: Astaneh Fault. (b) Simplified map of the main faults considered as active in Tehran region (modified after Nazari et al , 2010) with associated historical seismicity showing epicentral areas with the date, MSK intensity and estimated magnitude after the distribution and amount of damages (after Ambraseys and Melville [1982] and Berberian and Yeats [1999]). Grey: Alborz reliefs; White: alluvial piedmont; black lines with triangles: thrust faults; black lines with arrows: strike‐slip faults; dashed lines: uncertain active faults.…”
Section: Introductionmentioning
confidence: 99%